Approaches to assessing shoulder pain. - Dean, B (BMJ Publishing Group, 2017)
Gray and colleagues recommend a three step approach in assessing shoulder pain for non-specialists. I would point readers to the methodologically robust review by Hermans et al summarising the evidence for the various special tests in diagnosing rotator cuff tendinopathy.